2021
DOI: 10.1371/journal.pone.0247474
|View full text |Cite
|
Sign up to set email alerts
|

Association between a complex community intervention and quality of health extension workers’ performance to correctly classify common childhood illnesses in four regions of Ethiopia

Abstract: Background Due to low care utilization, a complex intervention was done for two years to optimize the Ethiopian Health Extension Program. Improved quality of the integrated community case management services was an intermediate outcome of this intervention through community education and mobilization, capacity building of health workers, and strengthening of district ownership and accountability of sick child services. We evaluated the association between the intervention and the health extension workers’ abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
5
1
Order By: Relevance
“…In the current study, the involvement of woreda administrators in HEWs supervision also did not show any significant association with improving NCD prevention service coverage. While some studies found results like ours, 37 the absence of association in the current research is contrary to evidence that supportive supervision is critical for programme success and effective NCD service delivery by CHWs. 14 17 24 As evidence suggests, supervision needs to be linked to performance goals, targeted to a specific group and focused on particular knowledge and skillset to have the desired effect.…”
Section: Bmj Global Healthcontrasting
confidence: 99%
“…In the current study, the involvement of woreda administrators in HEWs supervision also did not show any significant association with improving NCD prevention service coverage. While some studies found results like ours, 37 the absence of association in the current research is contrary to evidence that supportive supervision is critical for programme success and effective NCD service delivery by CHWs. 14 17 24 As evidence suggests, supervision needs to be linked to performance goals, targeted to a specific group and focused on particular knowledge and skillset to have the desired effect.…”
Section: Bmj Global Healthcontrasting
confidence: 99%
“…23 Unfortunately, the intervention, which included community engagement, training, supportive supervision and performance reviews of health workers neither increased care-seeking for sick children 24 nor improved the classification of childhood illnesses by these primary healthcare workers. 25 The failure of such an intervention could, at least partly, be attributed to the context of the health extension workers. There is a need for accurate measurements that reflect the health system context in which care is provided to patients and populations.…”
Section: Introductionmentioning
confidence: 99%
“…The intervention had no effect on household participation in community engagement forums, nor on indicators of district accountability of child health services [ 32 ]. Another study based on the same survey data also revealed a lack of association between the intervention and correct classification of sick children 2–59 months by the health extension workers as compared to health officers who served as a gold standard [ 58 ].…”
Section: Discussionmentioning
confidence: 99%